A Cross-Sectional Study Exploring Mental Health among Patients Suffering from Dengue in Pakistani Tertiary Care Hospitals - null Faiza; Fatima Jawad; Namra Chaudhary; Mahnoor Younas; Sadaf Fatima; Fiza Ayub; Allah Bukhsh Awan; Tahir Mehmood Khan (Mental Illness)
Background. Dengue, known as “Tropical flu,” is a widespread disease that has recently become endemic in many Asian countries. Dengue disease still lacks research in many aspects, specifically the impact of patient factors and disease prognosis on mental health. This is a cross-sectional study that evaluated the impact of different patient factors on depression, stress, and anxiety in patients with acute dengue infection. Methods. An interview-based data were collected through a questionnaire containing patient sociodemographic parameters, clinical parameters, and DASS 21 questions. Independent sample T-test, one-way ANOVA test, and post hoc test were performed to determine the degree of association of psychological manifestations with clinical signs and symptoms considering a level of significance of p<0.05. Results. The patients from 39 years to 49 years of age had a higher association with stress, depression, and anxiety. The participants at primary and matriculation level education had a higher association with dengue-associated anxiety. Among the three levels of fever, i.e., mild (<102°F), moderate (102-103°F), and severe (>103°F), the participants suffering from severe fever experienced more anxiety and so was those with intense pain and stress. Conclusions. According to the DASS-21 tool, patients with severe pain and high-degree fever during dengue had significant stress and anxiety symptoms, respectively, than the patients with mild or moderate pain and fever. Middle-aged patients with low literacy levels were also found to have significant associations with stress, anxiety, and depression. To our knowledge, this is one of the first studies in Pakistan that in-depth explored the impact of patient factors’ variability on psychological illnesses related to dengue. These findings may warrant practitioners to integrate timely psychological screening and care for dengue patients.